Invariant Gametogenic Response of Dominant Infaunal Bivalves From the Arctic Under Ambient and Near-Future Climate Change Conditions - Reed, Adam J.; Godbold, Jasmin A.; Solan, Martin; Grange, Laura J. (Frontiers in Marine Science, 2021)
Arctic marine ecosystems are undergoing a series of major rapid adjustments to the regional amplification of climate change, but there is a paucity of knowledge about how changing environmental conditions might affect reproductive cycles of seafloor organisms. Shifts in species reproductive ecology may influence their entire life-cycle, and, ultimately, determine the persistence and distribution of taxa. Here, we investigate whether the combined effects of warming and ocean acidification based on near-future climate change projections affects the reproductive processes in benthic bivalves (Astarte crenata and Bathyarca glacialis) from the Barents Sea. Both species present large oocytes indicative of lecithotrophic or direct larval development after 4 months exposure to ambient (<2°C, 400 ppm [CO2]) and near-future (3 - 5°C, 550 ppm [CO2]) conditions, but we find no evidence that the combined effects affect the size frequency distribution of oocytes. Whilst our observations are indicative of resilience of this reproductive stage to global changes, we also highlight that the successful progression of gametogenesis under standard laboratory conditions does not necessarily mean that successful development and recruitment will occur in the natural environment. This is because the metabolic costs of changing environmental conditions are likely to be offset by, as is common practice in laboratory experiments, by feeding ad libitum. We discuss our findings in the context of changing food availability in the Arctic and conclude that, if we are to establish the vulnerability of species and ecosystems, there is a need for holistic approaches that incorporate multiple system responses to change.